EFEKTIVITAS INDUKSI REPRODUKSI Macrobachium Rosenbergi BETINA DENGAN KOMBINASI ABLASI UNILATERAL DAN SUPLEMENTASI VITAMIN E - Inayatsyah Inayatsyah; Rahmawati Nasution (Universitas Teuku Umar, 2016)
This study aims to Know the optimum dosage of vitamin E supplementation on feed for a long time ripe gonads, IKG, fecundity egg and larval survival on prawns female, And Knowing the optimum dose vitamin E supplementation on feed for a long time ripe gonads, IKG, fecundity eggs and larval survival in female prawns were ablated unilateral. This research was carried out experimentally, with the experimental design basic design completely randomized (CRD) factorial 2 x 4, consists of two factors: Prawn females ablation, consists of two levels: Prawns females without ablation (UGT), Prawns female ablation unilateral (UGA). The dose of vitamin E / kg feed, consisting of four levels: Vitamin E 0 IU / kg feed, vitamin E 200 IU / kg feed, vitamin E 400 IU / kg feed, vitamin E 600 IU / kg feed. The optimum dosage vitamin E supplementation of 600 IU on feed effective Time ripe for a review of the old gonads, IKG , egg fecundity and the degree of continuity of Life larvae prawns females. Supplementation of vitamin E at 200 IU at prawn the ablated females showed a unilateral already fecundity best eggs . Induction reproductive females with a combination of prawns unilateral ablation and vitamin E supplementation of 600 IU on feed effectively improve reproduction prawns.